PENGARUH MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLEKTING, EXTENDING) BERBANTUAN MEDIA DIGITAL TERHADAP HASIL BELAJAR IPA DI SDN CIJANTUNG 06 - Zafira Nurbillah; Ishaq Nuriadin (STKIP Subang, 2022)
This study aims to determine the effect of science learning outcomes using the CORE (Connecting, Organizing, Reflecting, Extending) learning model assisted by digital media in fourth grade students at SDN Cijantung 06. This research is a quantitative study using a Quasi Experimental research method with a Posttest-Only Control Group Design type. The population in this study were all fourth grade students at SDN Cijantung 06 in the even semester of the 2021-2022 academic year. The research sample consisted of 64 students from class IV-B and IV-C. The sampling technique in this study used the Cluster Random Sampling method. The research instrument was an objective test in the form of multiple choice questions consisting of 35 questions. The instrument was first tested at SDN Susukan 02 Pagi with 64 students. The calculation of the validity test uses the Biserial Point Correlation formula on 40 items in the form of multiple choice with 35 valid questions and 5 drop questions obtained. While the calculation of reliability test using KR-21 obtained of 0.85 with a very strong level of reliable interpretation. Furthermore, there is a requirement analysis test that is carried out, namely the normality test with the Lilliefors formula, then the data obtained are normally distributed from the experimental class and the control class. Then, the homogeneity test was calculated using Fisher's exact test to get the group variance data with homogeneous distribution. Then, hypothesis testing using t-test resulted in of 7,322 with a significant 5% which resulted in rejecting . The results of this study can be concluded that there is an influence of the CORE learning model (Connecting, Organizing, Reflecting, Extending) assisted by Digital Media on Science Learning Outcomes at SDN Cijantung 06.